Ischemic Stroke, Aortic Stenosis, Heart Failure with Complications Anemia and Hyponatremia - Cynthia; Diana Aulia (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2023)
Ischemic stroke is a circulatory disorder in brain is caused by reduced or stopped blood flow in some areas of brain. Aortic stenosis is a heart valve disorder characterized by remodeling progressive fibro-calcification and thickening of the aortic valve leaflets over the years, evolves that occur in an early aortic valve (tricuspid) or an abnormal aortic valve (bicuspid) cause severe obstruction to cardiac outflow. Heart failure is a complex clinical syndrome that can occur as result of heart problem structural or functional impairment that impairs the ability of the ventricles to fill or secrete adequate amounts of blood to meet the metabolic demands of the tissues. The patient had a diagnosis of compensatory dyspnea et causa aortic stenosis, right hemiparesis, and repair aphasia delivered to the laboratory from neurorestoration room on January 9th, 2018 for a complete hematology and electrolyte examination (Na+,K+, Cl-).